THE INFLUENCE OF AGILE LEADERSHIP, WORK ETHIC, AND WORKLOAD ON EMPLOYEE PERFORMANCE AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION IN PASURUAN REGENCY WITH WORK-LIFE BALANCE AS AN INTERVENING VARIABLE - Mukhammad Fauzan Aldi; Ida Aju Brahmasari, Ida Aju Brahma Ratih (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The study intends to illustrate and investigate the effects of agile leadership, work ethic, workload, and work-life balance on employee performance using the Pasuruan Regency's Population and Civil Registration Service as an intervening variable. A sample of 120 respondents and the population are used in this quantitative study design. Likert scales are used to measure data collected via questionnaires. The Partial Least Square (PLS) program is used in the analytical process after the Structural Equation Model (SEM) tool has been used. The findings of the study show that: 1. Agile leadership greatly enhances work-life balance for the Civil Registration Service and Population of the Pasuruan Regency. 2. Employee performance at the Pasuruan Regency's Population and Civil Registration Service is significantly improved by agile leadership. 3. At the Pasuruan Regency's Population and Civil Registration Service, a strong work ethic significantly improves work-life balance. 4. Employee performance in the Pasuruan Regency's Population and Civil Registration Service is significantly improved by a strong work ethic. 5. At the Pasuruan Regency's Population and Civil Registration Service, workload significantly improved work-life balance. 6. Employee performance in the Pasuruan Regency's Population and Civil Registration Service is unaffected by workload. 7. At the Pasuruan Regency's Population and Civil Registration Service, work-life balance significantly improves employee performance.